2017
DOI: 10.1007/s11356-017-9460-0
|View full text |Cite
|
Sign up to set email alerts
|

Chilling tolerance in three tomato transgenic lines overexpressing CBF3 gene controlled by a stress inducible promoter

Abstract: Plants integrate and monitor low temperature signals to cope with the continual variations in their environment. Arabidopsis thaliana cold responsive-element binding factor 3 (AtCBF3) plays its role in various cellular activities by modulating multiple genes induced under chilling stress. In this work, AtCBF3 transcription was remarkably induced following chilling stress. AtCBF3-overexpressors namely AtCBF3-Rio Grande, AtCBF3-Moneymaker, and AtCBF3-Roma showed defensible response to various levels of chilling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…For example, potato plants ectopically expressing AtCBF3 exhibit enhanced tolerance to high-temperature stress (Dou et al 2015). Tomato plants overexpressing AtCBF3 gene controlled by a stress inducible promoter shown enhanced chilling tolerance (Shah et al 2017) and the ectopic expression of AtCBF3 confers tolerance to drought in red sage (Wei et al 2016) Citrus trees are characterized by high water demand and acute sensitivity to salinity. Several studies have reported increased stress tolerance in transgenic lines of citrus species, including the expression of betaine aldehyde dehydrogenase from Atriplex hortensis in trifoliate orange (Fu et al 2011), the expression of yeast HAL2 in Carrizo citrange (Cervera et al 2000;Ali et al 2012), the expression of the glyoxylases genes BjGlyI and PgGlyII in Carrizo citrange (Álvarez-Gerding et al 2015a), and the expression of CBF3 from Arabidopsis in Citrus macrophylla (Álvarez-Gerding et al 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…For example, potato plants ectopically expressing AtCBF3 exhibit enhanced tolerance to high-temperature stress (Dou et al 2015). Tomato plants overexpressing AtCBF3 gene controlled by a stress inducible promoter shown enhanced chilling tolerance (Shah et al 2017) and the ectopic expression of AtCBF3 confers tolerance to drought in red sage (Wei et al 2016) Citrus trees are characterized by high water demand and acute sensitivity to salinity. Several studies have reported increased stress tolerance in transgenic lines of citrus species, including the expression of betaine aldehyde dehydrogenase from Atriplex hortensis in trifoliate orange (Fu et al 2011), the expression of yeast HAL2 in Carrizo citrange (Cervera et al 2000;Ali et al 2012), the expression of the glyoxylases genes BjGlyI and PgGlyII in Carrizo citrange (Álvarez-Gerding et al 2015a), and the expression of CBF3 from Arabidopsis in Citrus macrophylla (Álvarez-Gerding et al 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…When plants are exposed to cold environmental conditions, CRT binding factor (CBF) genes are rapidly induced to express and then activate the downstream target cold‐regulated ( COR ) genes or CBF‐regulated genes (Shi et al, 2017, 2018; Song et al, 2021; Tang et al, 2020). AtCBF1 to AtCBF3 transcription factors bind to DRE cis‐elements and induce COR genes expression (Maruyama et al, 2004; Shah et al, 2017; Vogel et al, 2005). AtDREB1A overexpressing Arabidopsis ( Arabidopsis thaliana ) exhibited a freezing tolerance phenotype (Gilmour et al, 2000), in which increased levels of proline, sucrose, and raffinose were also detected (Gilmour et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…As the main intracellular osmoregulatory substance, soluble sugars can reduce the cell water density to maintain cell water, decrease the cytoplasmic freezing point to resist the damage caused by low temperature to plant cells, and act as scavengers of reactive oxygen species to improve the cell membrane system stability (Bohnert & Sheveleva, 1998). Although there is a strong correlation between sugars and frost or cold resistance in plants, the sugars associated with freezing tolerance vary among plants (Shah et al, 2017; Yu et al, 2015). The treatment of rice seedlings with fructose or glucose before low‐temperature treatment can improve their cold resistance.…”
Section: Introductionmentioning
confidence: 99%